Impact of genome assembly status on ChIP-Seq and ChIP-PET data mapping - Sachs Laurent (BMC Research Notes, 2009)
Abstract Background ChIP-Seq and ChIP-PET can potentially be used with any genome for genome wide profiling of protein-DNA interaction sites. Unfortunately, it is probable that most genome assemblies will never reach the quality of the human genome assembly. Therefore, it remains to be determined whether ChIP-Seq and ChIP-PET are practicable with genome sequences other than a few (e.g. human and mouse). Findings Here, we used in silico simulations to assess the impact of completeness or fragmentation of genome assemblies on ChIP-Seq and ChIP-PET data mapping. Conclusions Most currently published genome assemblies are suitable for mapping the short sequence tags produced by ChIP-Seq or ChIP-PET.